Effects of minerals in ferric bauxite on sodium carbonate decomposition and volatilization - Hu, Wen-tao; Wang, Hua-jun; Liu, Xin-wei; Sun, Chuan-yao (Journal of Central South University, 2015)
Direct reduction is an emerging technology for ferric bauxite utilization. However, because of sodium volatilization, its sodium carbonate consumption is considerably higher than that in ordinary bauxite processing technology. TG-DSC and XRD were applied to detecting phase transformation and mass loss in direct reduction to reveal the mechanism on sodium volatilization. The results show that the most significant influence factor of ferric bauxite on sodium volatilization in direct reduction system is its iron content. Sodium volatilization is probably ascribed to the instability of amorphous substances structure. Amorphous substances are the intermediate-products of the reaction, and the volatilization rate of sodium increases with its generating rate. These amorphous substances are volatile, thus, more sodium is volatilized with its generation. A small amount of amorphous substances are generated in the reaction between Na 2 CO 3 and Al 2 O 3 ; thus, only 3.15% of sodium is volatilized. Similarly, the volatilization rate is 1.87% in the reaction between Na 2 CO 3 and SiO 2 . However, the volatilization rate reaches 7.64% in the reaction between Na 2 CO 3 and Fe 2 O 3 because of the generation of a large amount of amorphous substances.